2006
DOI: 10.1007/s00531-005-0010-5
|View full text |Cite
|
Sign up to set email alerts
|

New Early Permian paleomagnetic results from the Brive basin (French Massif Central) and their implications for Late Variscan tectonics

Abstract: In order to assess the structural evolution of the Brive basin and the Paleozoic activity of surrounding major faults in the French Massif Central, we carried out a paleomagnetic study

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…These findings are discussed in conjunction with data from the literature in quest for possible triggering mechanisms associated with Pangea instability and transformation during the late Paleozoic. To the west of the study area, a very similar timing of block rotations was observed in the Brive and Saint‐Affrique basins of the French Massif Central where Early Permian rocks show rotated paleomagnetic vectors while Late Permian rocks have not been affected by rotations [ Chen et al , 2006; see also Cogné et al , 1990, 1993; Diego ‐ Orozco and Henry , 1998; Henry et al , 1999; Diego ‐ Orozco et al , 2002]. Paleomagnetic data from the Maures‐Estérel massif located immediately to the east of our study area suggest a large clockwise block rotation during the Early to Middle Permian [ Edel , 2000].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…These findings are discussed in conjunction with data from the literature in quest for possible triggering mechanisms associated with Pangea instability and transformation during the late Paleozoic. To the west of the study area, a very similar timing of block rotations was observed in the Brive and Saint‐Affrique basins of the French Massif Central where Early Permian rocks show rotated paleomagnetic vectors while Late Permian rocks have not been affected by rotations [ Chen et al , 2006; see also Cogné et al , 1990, 1993; Diego ‐ Orozco and Henry , 1998; Henry et al , 1999; Diego ‐ Orozco et al , 2002]. Paleomagnetic data from the Maures‐Estérel massif located immediately to the east of our study area suggest a large clockwise block rotation during the Early to Middle Permian [ Edel , 2000].…”
Section: Discussionmentioning
confidence: 84%
“…The continental‐scale events of dextral shearing related to late Paleozoic Pangea instability should have left a fingerprint in the crustal structure of portions of southern Europe formerly located between Laurasia and Gondwana (Figures 1 and 2). For example, tectonic block rotations have been observed in Early Permian rocks from the French Massif Central, while Late Permian rocks from the same area are un‐rotated [ Chen et al , 2006, and references therein]; large rotations have also been documented in Late Carboniferous–Permian rocks from Maures‐Estérel in southern France and from Corsica‐Sardinia [ Edel , 2000; Emmer et al , 2005]; in Sardinia, recent paleomagnetic results indicate that these rotations should have occurred before Jurassic times [ Aubele et al , 2009; Kirscher et al , 2011].…”
Section: Introductionmentioning
confidence: 99%
“…The Triassic poles, instead, plot close to the Triassic segment of the European APWP and provide a strong constraint on the age of the observed rotations, which is likely late Early‐Middle Permian. To the west of Toulon‐Cuers, a very similar timing of block rotations was observed in the Lodève, Brive, and Saint‐Affrique basins of the French Massif Central where Early Permian rocks show rotated paleomagnetic vectors while Late Permian rocks have not been affected by rotations [ Merabet and Guillaume , ; Cogné et al ., ; Diego‐Orozco and Henry , ; Henry et al ., ; Diego‐Orozco et al ., ; Chen et al ., ]. In addition, paleomagnetic data from the Maures‐Estérel massif located immediately to the east of the study area in SE France suggest a large clockwise block rotation during the late Early to Middle Permian [ Edel , ].…”
Section: Discussionmentioning
confidence: 99%
“…They were therefore located just where most of the inferred shearing between Gondwana and Laurussia is expected to have taken place. We therefore speculate that post‐Variscan intra‐Pangea wrenching and shearing may have induced the large‐scale rotations of fault‐bounded blocks observed in Permian units of Sardinia as well as elsewhere in Europe, e.g., in the Saint‐Affrique and Brive basins of the French Massif Central [ Chen et al , 2006], as preliminarily discussed by Emmer et al [2005]. This inference, which remains at present speculative, however, will be explored in detail in a paleomagnetic work (now in progress) on Late Paleozoic–Middle Triassic rocks of Sardinia, which we consider as geological key witnesses of a major African‐European contact zone.…”
Section: Discussionmentioning
confidence: 99%